Acid‐Stable Nucleobase Protection for a Strongly Pairing Pyridone C‐Nucleoside Suitable for Solid‐Phase Synthesis of Oligonucleotides. Issue 27 (20th July 2022) - Eyberg, Juri; Göhringer, Daniela; Salihovic, Amila; Richert, Clemens
Abstract: Oligonucleotides are indispensable tools in diagnostics, therapeutic applications and molecular biology. The low base pairing strength of thymine with adenine complicates their use. Ethynylpyridone C ‐nucleosides are analogs of thymidine that pair more strongly and with improved base selectivity, and sequences containing these analogs show improved target affinity and selectivity, but their routine use is hampered by diminished yields of solid‐phase syntheses with the known building blocks. A partial loss of base protecting groups during the acidic deblocking step of chain extension cycles was identified as the cause of lower yields. Here we report the synthesis of an improved phosphoramidite building block featuring a pivaloyloxymethyl (POM) base protecting group. This building block gives oligonucleotides containing the strongly pairing ethynylmethylpyridone C ‐nucleoside in high yield and purity via solid‐phase synthesis. Abstract : A protecting group Scheme was developed that allows for high‐yielding solid‐phase syntheses of oligodeoxynucleotides with strongly pairing ethynylmethylpyridone base surrogates for thymine without the branching side reactions encountered with the known protection Scheme.